D–π–A Triarylboron Compounds with Tunable Push–Pull Character Achieved by Modification of Both the Donor and Acceptor Moieties. Issue 1 (20th November 2014) - Zhang, Zuolun; Edkins, Robert M.; Nitsch, Jörn; Fucke, Katharina; Eichhorn, Antonius; Steffen, Andreas; Wang, Yue; Marder, Todd B.
Abstract The push–pull character of a series of donor–bithienyl–acceptor compounds has been tuned by adopting triphenylamine or 1, 1, 7, 7‐tetramethyljulolidine as a donor and B(2, 6‐Me2‐4‐RC6H2)2 (R=Me, C6F5 or 3, 5‐(CF3)2C6H3) or B[2, 4, 6‐(CF3)3C6H2]2 as an acceptor. Ir‐catalyzed CH borylation was utilized in the derivatization of the boryl acceptors and the tetramethyljulolidine donor. The donor and acceptor strengths were evaluated by electrochemical and photophysical measurements. In solution, the compound with the strongest acceptor, B[2, 4, 6‐(CF3)3C6H2]2 ((FMes)2B), has strongly quenched emission, while all other compounds show efficient green to red (ΦF=0.80–1.00) or near‐IR (NIR; ΦF=0.27–0.48) emission, depending on solvent. Notably, this study presents the first examples of efficient NIR emission from three‐coordinate boron compounds. Efficient solid‐state red emission was observed for some derivatives, and interesting aggregation‐induced emission of the (FMes)2B‐containing compound was studied. Moreover, each compound showed a strong and clearly visible response to fluoride addition, with either a large emission‐color change or turn‐on fluorescence.